People’s participation and convergence of Institutions in watershed development in eastern ghats of India: An experience - Sudhishri, Susama; Dass, Anchal; Choudhury, P.R.; Kumar, Pramod; Lenka, N.K.; Patnaik, U.S. (Annals of Agricultural Research, 2016)
Participatory integrated watershed management is considered to be an ideal way of sustainableÂ development. It emphasizes on the participation and contribution of the stakeholders in terms ofÂ cash and kind. For wide spreading of the technologies and use of financial capital in a very extensiveÂ way convergence of line departments plays an important role. The present paper is based on theÂ outcome and experiences gained, while applying such theses for the sustainable holistic developmentÂ of a tribal watershed, Kokriguda, in Koraput district of Odisha falling in the eastern ghats region ofÂ India. A number of interventions were undertaken based on the problems, perceptions, needs andÂ priorities of the villagers as per PRA exercises. Persistent efforts and enduring patience of themÂ watershed development team could win their faith. Different entry point activities (EPAs) provedÂ fruitful in providing further impetus to the participation process by converging different institutionsÂ in the vicinity. Obviously, gaining confidence and motivation of the community were the naturalÂ offshoots of the EPA. Strengthening of local institutions viz. Watershed Association (WA), WatershedÂ Committee (WC), Self Help Groups (SHGs), User Groups (UGs), Water User’s Association (WUA),Â etc. and converging all line departments were the associated complementary measures. The villagersÂ extended their contribution in the form of labour ranging from 5-100% in different interventions.